EVALUATION OF BIOPHARMACEUTICAL AND PHARMACOLOGICAL PROPERTIES OF COMBINED TERNARY COMPONENTIAL ANALGESIC TABLETS - YUNUSOVA, KHOLIDA; RAVSHANOVA, SEVARA (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to investigate the biopharmaceutical and pharmacological features of the recommended combined tablets using in vivo and in vitro methodologies. We previously developed technology for obtaining combined ternary tablets with a potential analgesic effect. In vitro experimental analyses were performed on a rotating basket instrument included in the State Pharmacopoeia XI (SPh XI). Based on the results of studying the effect of pH on the dissolution rate of the recommended tablets, the use of a neutral medium—purified water—is recommended for further studies. From a biopharmaceutical point of view, the basket rotation speed is 100 turnovers per minute. The acute toxicity of the compared drugs was studied by the generally accepted method described in the literature: a single administration with the determination of the toxicity class. The analgesic effect of the drug was studied on white outbred mice in the amount of 18 animals, weighing 20–23 grams. A specific pain reaction, "cramps" (characteristic movements of animals, including contractions of the abdominal muscles, alternating with their relaxation, stretching of the hind limbs, and flexing of the back), was caused by intraperitoneal administration of 0.75% acetic acid (0.1 ml/10 g body weight). The antipyretic effect of the drugs was evaluated in rats weighing 180–200 g. Body temperature is excited by intravenous administration of Pyrogenal. The experimental study of the indicators of acute toxicity and specific activity of the recommended combined tablets performed in comparison with the tablets Metamizole Sodium 500 mg tablets (under the brand name “Analgin”).